Corporate Culture in Preschool Organisation Administration: European and Asian Context - Abram Burnell; Vera Pozsgay; Iryna S. Kravets (Mukachevo State University, 2021)
The relevance of the study lies in the need to introduce corporate culture in the field of preschool education to improve the managerial level and pedagogical compliance of employees who influence the development of preschool children as individual members of society. The purpose of the study is to analyse organisational culture in the administration of preschool institutions, based on a comparison of Asian and European cultural paradigms. The research consisted of two stages, namely theoretical and empirical, and involved the use of general scientific research methods, including analysis, synthesis, comparison, systematisation, questionnaires, surveys, and statistical data processing. In the course of the study, foreign scientific literature was analysed in order to determine the phenomena of preschool institution administration and its corporate culture. An empirical study was conducted, the essence of which was an online survey among kindergarten administrators in Germany and Kazakhstan. It is determined that both the German and Kazakh corporate administration cultures have weaknesses, common to which is the lack of full-fledged freedom in decision-making and conducting activities. It was discovered that the two countries have a common view on the development of administrator's corporate competencies, including strategic importance, change management, leadership, performance management, learning orientation, responsibility, focus on results, activity, and social intelligence. It is confirmed that German kindergarten heads are distinguished by their productivity and focus on learning, while Kazakh ones attempt to pay attention to responsibility and thoroughness. The practical value of the research is to compare two views on the corporate administration culture in preschool organisations in the context of European and Asian paradigms